Local Language Maintenance: A Cultural and Sociolinguistic Perspective - Iwan; Syarif Hidayat; Imam Miftahul Jannah (CV. Goresan Pena, 2023)
Local language as a cultural treasure is very different from the sociolinguistic perspective. Culture positions local languages as wealth and relics of human creativity and karsa in the past which are very meaningful and must be maintained and preserved. When correlated with the nature of culture, of course, local languages are included in a dynamic culture which means that they will experience language deconstruction and/or reconstruction. It is impossible if the language does not accept a concept or vocabulary from another language. This means that the language will experience development both in terms of the vocabulary it has or the concept and its use. The use of language must be positioned not only as a tool for communication but as a cultural result that must be maintained and preserved. This paper tries to explain how local language preservation occurs in Indonesia in the realm of culture and sociolinguistics.